Utility of gamma‐glutamyl transpeptidase to lymphocyte count ratio in predicting prognosis of patients with oral cancer: A prospective cohort study in Southeastern China. Issue 5 (7th March 2023) - Wang, Na; Lin, Yulan; Chen, Fa; Liu, Fengqiong; Wang, Jing; Gao, Bingju; Qiu, Yu; Lin, Lisong; Shi, Bin; He, Baochang
Abstract: Background: To assess the prognostic role of gamma‐glutamyl transpeptidase to lymphocyte count ratio (GLR) and develop a prognostic nomogram for patients with oral cancer. Methods: A prospective cohort ( n  = 1011) was conducted during July 2002 to March 2021 in Southeastern China. Results: The median follow‐up time was 3.5 years. Multivariate Cox regression (OS: HR = 1.51, 95% CI: 1.04, 2.18) and Fine–Gray model (DSS: HR = 1.68, 95% CI: 1.14, 2.49) both showed that high GLR could act as an indicator of poor prognosis. A nonlinear dose–response relationship was observed between continuous GLR and the risk of all‐cause mortality ( p for overall = 0.028, p for nonlinear = 0.048). Compare with TNM stage, time‐dependent ROC curve proved that GLR‐based nomogram model performs better in predicting prognosis (the area under curve for 1‐, 3‐, and 5‐years mortality: 0.63, 0.65, and 0.64 vs. 0.76, 0.77, and 0.78, p  < 0.001). Conclusion: GLR might be a useful tool in predicting prognosis for patients with oral cancer.